Influência dos direcionadores na violação dos covenants contábeis nas empresas do setor de utilidade pública e bens industriais - Fonseca, Kellma Bianca Cardoso (2021)
The accounting-based covenants are contracting terms established in debt agréments, generally expressed in accounting ratios, intending to restrict debtor’s activities. The covenants function is to reduce both the acting conflicts and uncertainties regarding company future performance. After consulting academic literature, it was observed that the covenants drivers represent a information set allowing to follow company financial performance. However, studies identifiying all the covenants’ drivers related to these restrictive terms violation, concerning public utility sector and industrial goods were not found. Thus, this study objective is to identify and analyze which covenants drivers influence the probability of companies violating the contractual terms. When the company fails to comply with the contractual clauses established in the contracts, covenants are broken and creditors are entitled to demand the company's immediate debt settlement, resulting in consequences for the company. To identify which drivers influence the probability of breach of covenants, the explanatory notes of companies belonging to the public utility and industrial goods sector were analyzed to verify those that had these contractual clauses and, subsequently, the data was collected through Economática to calculate the drivers of the covenants.The results indicate the following variables influencing covenants violation: Total Assets, Financial Expense, Short-Term Loans, Total Net Debt, Equity, Financial Result, Long-Term Loans and Audit. These results are useful to managers, shareholders and creditors, as they reveal informations on financial performance, companies capacity to honor their financial commitments. Furthermore, they also serve as indicators to assess the possibility of contractual terms violation.